Pengaruh Persepsi Siswa tentang Penggunaan Learning Management System terhadap Motivasi Belajar Siswa pada Mata Pelajaran Pemograman Dasar SMKN 2 Padang dalam Masa Pandemi Covid-19 - Herzi Marta Gustan; Sofia Edriati; Irsyadunas Irsyadunas (Horizon, 2021)
One of the subjects that use learning management system is basic programming. “Based on data obtained from” teachers in the field of basic programming studies, there are still many students who have not completed subjects using learning management systems. The purpose of the study was to find out the influence of students' perceptions about the use of learning management systems on basic programming subjects on students' learning motivation in SMK Negeri 2 Padang “during the Covid-19 pandemic”. “The population in this study is all students of class x rpl odd semester of the academic year” 2020/2021 SMK Negeri 2 Padang consisting of two classes of 66 people. “Sampling in this study was conducted with simple random sampling techniques. The analysis method uses simple linear regression analysis. The results of the study found that the t count was 2,953 and the value (sig = 0.004< 0.05). With df = 36-2 = 34 Obtained a certificate of 1,691,” from the above results can be concluded students' perceptions about the use of learning management system in basic programming subjects affect student learning motivation in SMK Negeri 2 Padang in the Covid-19 Pandemic Period.